The Use of Ferromagnetic Screens in the Cathode of a Pulse-Periodic Relativistic Magnetron; Instruments and Experimental Techniques; Vol. 61, iss. 1 - Vintizenko I. I. Igor Igorevich (2018, 2018)
Title screen